IDENTIFIKASI SPESIES ORCHIDACEAE DI BLOK KOLEKSI TAMAN HUTAN RAYA WAN ABDUL RACHMAN LAMPUNG, INDONESIA - Ambarwati Ambarwati; Indriyanto Indriyanto; Yusnita Yusnita (Jurnal Hutan Tropis, 2019)
Wan  Abdul  Rachman  Forest  Park  is  a  nature  conservation  area  in  Lampung Province, Indonesia, which is devided into five large blocks, one of which is the collection block for  plants  and  animal.  The  function  of this  collection  block  is  for  area  of  plant  and  animal collection,  protection,  and  conservation.  One  focus  of  interest  of  the  plant collection  and conservation in the collection block of this Forest Park is Orchidaceae, since this flowering plant family has large diversity. In the past, this collection block was park of the primary forest. Due to land  clearing  by  the  surrounding  community,  currently  this  area  became  a  mixed  forest. Therefore, a study of orchid identification in this block is needed to know the current and actual orchid diversity, density and distribution  in this area. The research was conducted since March to April 2018 in area of 141,18 ha of the collection block. Using 2% of sampling intensity, data of orchid were  collected  by  surveying  the  area  using  a  line-plot method  consisting  a  total  of  70 plots. The  results  showed  that  there were a  total of 29 epiphytic orchid plants  identified as 8 species, namely Dendrobium subulatum, Dendrobium phalaenopsis, Dendrobium crumenatum, Adenoncos  elongata,  Liparis  lacerata,  Cymbidium  finlaysonianum,  Eria  javanica,  Thecostele alata, and 3 genera, namely Cymbidium sp., Coelogyne sp., and Cleisostoma sp. Those orchid species or genera were  living on 7 species of host plants with density varied  from 0.36 – 3.21 plants  per  ha.  Orchid  species  with  the  highest  densities  were  Dendrobium  subulatum (3.6 plants/ha).